Optimized dynamic line scanning thermography for aircraft structures. Issue 3 (2nd October 2019) - Peeters, Jeroen; Verspeek, S.; Sels, S.; Bogaerts, B.; Steenackers, G.
ABSTRACT: In-line inspection of advanced components, remains a challenging task in industry. A methodology is discussed which uses numerical simulations to automatically determine the best set of experimental parameters to inspect the structure on defects using active thermography. The inspection is performed using an industrial conveyor belt or a robotic arm optimized using a numerical model of the defected test sample. During the path planning, the directional emissivity is considered for the complex surface and an optimal experimental setup is found. The results show that in-line quality evaluation of complex shaped structures is improved with a minimal amount of inspection time.